Medical Speak , Expression of Medical Jargons and Slangs in English - Rasulova Nilufar Abduvossiyevna (Zien Journals, 2022)
Professional jargon is an integral part of the vocabulary of any specialist, including physicians, who speak any language. Doctors are known for their “black” jokes, so some of their professionalism may seem offensive to patients. Therefore, it is useful to study medical jargon even for people who have nothing to do with medicine.
Keywords: slang; jargon; professionalism; vegetable garden